Integrated approach to the understanding of the degradation of an urban river: local perceptions, environmental parameters and geoprocessing - Collier, Carolina A.; Almeida Neto, Miguel S. de; Aretakis, Gabriela MA; Santos, Rangel E.; de Oliveira, Tiago H.; Mourão, José S.; Severi, William; El-Deir, Ana CA (Journal of ethnobiology and ethnomedicine, 2015)
The use of interdisciplinary approaches such as the proposed report provides a broad understanding of the relationship between people and the environment, revealing reliable aspects not previously considered in the study of this relationship. This study compiled evidence on the environmental degradation of an urbanized river over the past few decades, providing a diagnosis of the consequences of this process for the river, its ichthyofauna, and the local human population. The study was focused on the Beira Rio community on the Capibaribe River in the municipality of São Lourenço da Mata, Pernambuco, Brazil. Data were collected using geoprocessing and ethnobiological approaches, as well as environmental parameters. This research was conducted with the most experienced long-term residents in the local community, through interviews and participatory methodologies to recovering information about the river environment, its ichthyofauna and its environmental services for the last decades. According to the GIS analysis, the study area was subject to an accelerated process of urbanization, with the total urban area increasing from 73 565, 98 m(2) in 1974 to 383 363, 6 m(2) in 2005. The informants perceived the urban growth, especially in the late twentieth century, being this period recognized as the phase of greatest negative changes in the river environment. The perceived decline of fish stocks was indicated by the community as one of the effects of river degradation. According to the interviews, the deterioration of the river affected the ecosystem services and the relationship of the adjacent human community with this ecosystem. The environmental data indicated that the river is suffering eutrophization and has fecal coliform concentrations 160 times higher than the maximum level permitted by Brazilian legislation. The interdisciplinary approach used in this research allowed the understanding of the degradation process of an urban river and some negative effects through the integration of environmental data, GIS and the local knowledge, revealing the complementarity of obtained data and the effectiveness of implementation of this approach.